Management of Waqf Assets for the Welfare of the Community in the Perspectives of Maqāṣid al-Sharī’ah: A Case Study on Muhammadiyah Institution - Sati, Ali; Tambunan, Syafrianto (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article aims to analyze the development of the waqf institution in Indonesia, with a particular emphasis on Muhammadiyah, which has experienced significant advancements in waqf governance and asset consolidation throughout the country. Muhammadiyah, as an organization, holds substantial promise for enhancing waqf in Indonesia, given its strategically important assets that carry significant economic value. Nonetheless, in various areas such as Aceh, West Sumatra, and Makassar, there are obstacles that contribute to the stagnation of the Muhammadiyah organization in terms of waqf governance. This study represents an empirical legal examination employing a maqāṣid al-sharī’ah framework. Information was collected via literature reviews and in-depth interviews with relevant participants, such as Muhammadiyah administrators and waqf managers. This analysis indicates that the Muhammadiyah organization has not effectively managed waqf, as demonstrated by numerous unrecorded waqf assets and various legal disputes. This arises from shortcomings in management, challenges related to human resources, and insufficient collaboration between institutions. The Waqf necessitates a legal framework that facilitates its growth and development, rather than one that imposes burdens. Furthermore, the importance of waqf socialization within the society is essential for the progress of waqf through mainstream media. Considering the principles of maqāṣid al-sharī’ah, Muhammadiyah, as an organization focused on enhancing education, social welfare, economics, and health, has significantly impacted the well-being of the Indonesian people.